Eksistensi Kurikulum Pesantren di Era 4.0 - Thoyyib, M; Ridlwan, Mujib; Ahmad Faiz Abdillah (Institut Agama Islam Al-Hikmah Tuban, 2023)
Abstract: The pesantren curriculum is a curriculum adopted from the Islamic boarding school learning system so that in learning it emphasizes the religiosity side which is marked by the large portion of religious education subjects. The industrial revolution 4.0 as an era of technological progress has had various negative impacts on the younger generation such as the eroding of religious values ​​in students so that they find it difficult to distinguish good things from bad things which causes students to easily be carried away by the negative currents of digitalization. The implementation of the pesantren curriculum in formal educational institutions can help schools shape the character and morals of students in facing the challenges of the times so that schools are expected to produce intelligent generations both intellectually and spiritually. Even though it originates from the pesantren curriculum, it has a dynamic nature and can accept positive new things so that it is always able to keep up with the times and still exist in the world of Indonesian education, this is evident from the ever-increasing tension in schools that adhere to the pesantren curriculum from time to time. Keywords: Curriculum, pesantren, era 4.0